I suppose you mean
![g(x) = \dfrac x{2\sqrt{36-x^2}} + 18\sin^{-1}\left(\dfrac x6\right)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%5Cdfrac%20x%7B2%5Csqrt%7B36-x%5E2%7D%7D%20%2B%2018%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29)
Differentiate one term at a time.
Rewrite the first term as
![\dfrac x{2\sqrt{36-x^2}} = \dfrac12 x(36-x^2)^{-1/2}](https://tex.z-dn.net/?f=%5Cdfrac%20x%7B2%5Csqrt%7B36-x%5E2%7D%7D%20%3D%20%5Cdfrac12%20x%2836-x%5E2%29%5E%7B-1%2F2%7D)
Then the product rule says
![\left(\dfrac12 x(36-x^2)^{-1/2}\right)' = \dfrac12 x' (36-x^2)^{-1/2} + \dfrac12 x \left((36-x^2)^{-1/2}\right)'](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac12%20x%2836-x%5E2%29%5E%7B-1%2F2%7D%5Cright%29%27%20%3D%20%5Cdfrac12%20x%27%20%2836-x%5E2%29%5E%7B-1%2F2%7D%20%2B%20%5Cdfrac12%20x%20%5Cleft%28%2836-x%5E2%29%5E%7B-1%2F2%7D%5Cright%29%27)
Then with the power and chain rules,
![\left(\dfrac12 x(36-x^2)^{-1/2}\right)' = \dfrac12 (36-x^2)^{-1/2} + \dfrac12\left(-\dfrac12\right) x (36-x^2)^{-3/2}(36-x^2)' \\\\ \left(\dfrac12 x(36-x^2)^{-1/2}\right)' = \dfrac12 (36-x^2)^{-1/2} - \dfrac14 x (36-x^2)^{-3/2} (-2x) \\\\ \left(\dfrac12 x(36-x^2)^{-1/2}\right)' = \dfrac12 (36-x^2)^{-1/2} + \dfrac12 x^2 (36-x^2)^{-3/2}](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac12%20x%2836-x%5E2%29%5E%7B-1%2F2%7D%5Cright%29%27%20%3D%20%5Cdfrac12%20%2836-x%5E2%29%5E%7B-1%2F2%7D%20%2B%20%5Cdfrac12%5Cleft%28-%5Cdfrac12%5Cright%29%20x%20%2836-x%5E2%29%5E%7B-3%2F2%7D%2836-x%5E2%29%27%20%5C%5C%5C%5C%20%5Cleft%28%5Cdfrac12%20x%2836-x%5E2%29%5E%7B-1%2F2%7D%5Cright%29%27%20%3D%20%5Cdfrac12%20%2836-x%5E2%29%5E%7B-1%2F2%7D%20-%20%5Cdfrac14%20x%20%2836-x%5E2%29%5E%7B-3%2F2%7D%20%28-2x%29%20%5C%5C%5C%5C%20%5Cleft%28%5Cdfrac12%20x%2836-x%5E2%29%5E%7B-1%2F2%7D%5Cright%29%27%20%3D%20%5Cdfrac12%20%2836-x%5E2%29%5E%7B-1%2F2%7D%20%2B%20%5Cdfrac12%20x%5E2%20%2836-x%5E2%29%5E%7B-3%2F2%7D)
Simplify this a bit by factoring out
:
![\left(\dfrac12 x(36-x^2)^{-1/2}\right)' = \dfrac12 (36-x^2)^{-3/2} \left((36-x^2) + x^2\right) = 18 (36-x^2)^{-3/2}](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac12%20x%2836-x%5E2%29%5E%7B-1%2F2%7D%5Cright%29%27%20%3D%20%5Cdfrac12%20%2836-x%5E2%29%5E%7B-3%2F2%7D%20%5Cleft%28%2836-x%5E2%29%20%2B%20x%5E2%5Cright%29%20%3D%2018%20%2836-x%5E2%29%5E%7B-3%2F2%7D)
For the second term, recall that
![\left(\sin^{-1}(x)\right)' = \dfrac1{\sqrt{1-x^2}}](https://tex.z-dn.net/?f=%5Cleft%28%5Csin%5E%7B-1%7D%28x%29%5Cright%29%27%20%3D%20%5Cdfrac1%7B%5Csqrt%7B1-x%5E2%7D%7D)
Then by the chain rule,
![\left(18\sin^{-1}\left(\dfrac x6\right)\right)' = 18 \left(\sin^{-1}\left(\dfrac x6\right)\right)' \\\\ \left(18\sin^{-1}\left(\dfrac x6\right)\right)' = \dfrac{18\left(\frac x6\right)'}{\sqrt{1 - \left(\frac x6\right)^2}} \\\\ \left(18\sin^{-1}\left(\dfrac x6\right)\right)' = \dfrac{18\left(\frac16\right)}{\sqrt{1 - \frac{x^2}{36}}} \\\\ \left(18\sin^{-1}\left(\dfrac x6\right)\right)' = \dfrac{3}{\frac16\sqrt{36 - x^2}} \\\\ \left(18\sin^{-1}\left(\dfrac x6\right)\right)' = \dfrac{18}{\sqrt{36 - x^2}} = 18 (36-x^2)^{-1/2}](https://tex.z-dn.net/?f=%5Cleft%2818%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29%5Cright%29%27%20%3D%2018%20%5Cleft%28%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29%5Cright%29%27%20%5C%5C%5C%5C%20%5Cleft%2818%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29%5Cright%29%27%20%3D%20%5Cdfrac%7B18%5Cleft%28%5Cfrac%20x6%5Cright%29%27%7D%7B%5Csqrt%7B1%20-%20%5Cleft%28%5Cfrac%20x6%5Cright%29%5E2%7D%7D%20%5C%5C%5C%5C%20%5Cleft%2818%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29%5Cright%29%27%20%3D%20%5Cdfrac%7B18%5Cleft%28%5Cfrac16%5Cright%29%7D%7B%5Csqrt%7B1%20-%20%5Cfrac%7Bx%5E2%7D%7B36%7D%7D%7D%20%5C%5C%5C%5C%20%5Cleft%2818%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29%5Cright%29%27%20%3D%20%5Cdfrac%7B3%7D%7B%5Cfrac16%5Csqrt%7B36%20-%20x%5E2%7D%7D%20%5C%5C%5C%5C%20%5Cleft%2818%5Csin%5E%7B-1%7D%5Cleft%28%5Cdfrac%20x6%5Cright%29%5Cright%29%27%20%3D%20%5Cdfrac%7B18%7D%7B%5Csqrt%7B36%20-%20x%5E2%7D%7D%20%3D%2018%20%2836-x%5E2%29%5E%7B-1%2F2%7D)
So we have
![g'(x) = 18 (36-x^2)^{-3/2} + 18 (36-x^2)^{-1/2}](https://tex.z-dn.net/?f=g%27%28x%29%20%3D%2018%20%2836-x%5E2%29%5E%7B-3%2F2%7D%20%2B%2018%20%2836-x%5E2%29%5E%7B-1%2F2%7D)
and we can simplify this by factoring out
to end up with
![g'(x) = 18(36-x^2)^{-3/2} \left(1 + (36-x^2)\right) = \boxed{18 (36 - x^2)^{-3/2} (37-x^2)}](https://tex.z-dn.net/?f=g%27%28x%29%20%3D%2018%2836-x%5E2%29%5E%7B-3%2F2%7D%20%5Cleft%281%20%2B%20%2836-x%5E2%29%5Cright%29%20%3D%20%5Cboxed%7B18%20%2836%20-%20x%5E2%29%5E%7B-3%2F2%7D%20%2837-x%5E2%29%7D)
A.) A = 20000 + 1000n
B = 20000(1.04)^n
b.) For A, sn = n/2(2a + (n - 1)d)
s20 = 20/2(2(20000) + 1000(20 - 1)) = 10(40000 + 19(1000)) = 10(40000 + 19000) = 10(59000) = $590,000
For B, sn = a(r^n - 1)/(r - 1)
s20 = 20000((1.04)^20 - 1)/(1.04 - 1) = 20000(2.191 - 1)/0.04 = 20000(1.191)/0.04 = 23822.46 / 0.04 = $595,561.57
c.) Using a graphing calculator, it takes 18 years for the
<span>total amount earned a company B is greater that the total amount of earned at company A.</span>
Answer: $3.8 per pound of food.
Step-by-step explanation: 18.24 divided by 4.8
The factors of 12 are 1, 2, 3, 4, 6, and 12 .
The factors of 32 are 1, 2, 4, 8, 16, and 32 .